2015
DOI: 10.1111/odi.12371
|View full text |Cite
|
Sign up to set email alerts
|

Novel anticoagulants: general overview and practical considerations for dental practitioners

Abstract: Currently, 4 novel Direct Oral Anticoagulants (DOACs) were approved by the FDA. This review focuses on these agents and proposes a matrix for the general dentists to assess bleeding risk in dental management of patient on DOACs. The outline covers the pharmacology of DOACs (rivaroxaban, apixaban, edoxaban and dabigatran), bleeding complications, risk associated with discontinuation, monitoring/reversal, and implications for the dental practitioners. A total of 18 randomized controlled trials were identified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 48 publications
2
55
0
2
Order By: Relevance
“…Recent reviews [2][3][4] have not identified any randomised controlled trials, case-control studies or systematic reviews of the new drugs in patients having dental procedures. There is no firm clinical evidence on which to base a decision to either continue or discontinue the drugs before invasive dental treatment.…”
Section: Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews [2][3][4] have not identified any randomised controlled trials, case-control studies or systematic reviews of the new drugs in patients having dental procedures. There is no firm clinical evidence on which to base a decision to either continue or discontinue the drugs before invasive dental treatment.…”
Section: Guidelinesmentioning
confidence: 99%
“…There is no firm clinical evidence on which to base a decision to either continue or discontinue the drugs before invasive dental treatment. To date, all published guidelines have been based purely on expert opinion and the consensus of multidisciplinary writing groups [4][5][6][7] or on clinical experience. 8 All guidelines recommend that dentists should take a cautious approach when performing invasive dental treatments for patients taking the new anticoagulants.…”
Section: Guidelinesmentioning
confidence: 99%
“…Procedures associated with an increased risk of bleeding such as multiple dental extractions, more invasive oral surgery (such as the use of local flaps or wide local excision of a tumour) and more invasive head and neck or salivary gland surgery requires a multidisciplinary team approach pre‐operatively, and discussion with haematology colleagues in complex cases . In these situations, the NOAC drug may need to be stopped for a period prior to surgery and in patients with a high thrombotic risk, continued anticoagulation with another agent (such as a low molecular weight heparin derivative) may need to be considered (Fig. ).…”
Section: Monitorisation and Oral Management Of Patients On Noacsmentioning
confidence: 99%
“…Većinu stomatoloških krvarenja moguće je sanirati sa kompresijom ili hirurškom suturom. Ukoliko je potrebno, moguće je odložiti dozu NOAK-a, izostaviti jednu dozu leka ili prekinuti lek na 24-48h 17 .…”
Section: Antiplatelet and Anticoagulant Medications And Dental Procedunclassified
“…Individual assessment of each patient is required depending on comorbidity and planned dental intervention.The majority of dental bleeding can be stopped with local measures such as mechanical compression or suturing. If necessary, it is possible to postpone a dose of NOAC, skip one dose or discontinue the drug for 24-48h 17 .…”
Section: Prevencija Pojave Bakterijskog Endokarditisa Tokom Stomatolomentioning
confidence: 99%